Analysis of a rectangular prism n-units RLC fractional-order circuit network - Chen, Liping (2021)
It was demonstrated recently that ideal capacitors can not exist physically and that the behavior of real-world inductors and capacitors is characterized by fractional-order (FO) models. Therefore, the modeling and analysis of FO electrical circuit networks (FO-ECN) has gained considerable interest. This paper introduces the basic principles of a class of rectangular prism n-units () RLC FO-ECN, including the mathematical modeling and the analysis of the impedance magnitude and phase. Three general formulas of the equivalent impedance between two nodes of the FO-ECN are obtained by the matrix transform method. The relationship between the impedance and the FO-ECN parameters, including the capacitance, inductance, number of circuit units and FO are investigated. Numerical simulations reveal dynamical phenomena not exhibited by ordinary ECN.